Pengaruh Kepercayaan Diri, Minat Belajar, dan Peran Orang Tua terhadap Kemampuan Berbicara Siswa Pada Materi Teks Negosiasi Kelas X SMAN 10 Samarinda - Fitriani Nasir; Azainil Azainil; Yusak Hudiyono (Universitas Mulawarman, 2023)
This research aims to find out the influence of (1) self-confidence; (2) learning interest; (3) parental support; and (4) self-confidence, learning interests, and parental support; on negotiation speaking ability. The method used in this study is ex post facto. The sample used amounted to 204 students from the student population of class X SMAN 10 Samarinda. The analysis techniques in this study used regression models. The following research results were obtained based on the data analysis results. First, there is an influence between self-confidence in the ability to speak on the material of the student's negotiation text based on Sig grades. 0.000. Second, there is no influence between learning interests and the ability to speak on the student's negotiation text material based on Sig grades. 0.136. Third, there is an influence between parental support on the ability to speak on the material of the student's negotiation text based on Sig grades. 0.007. Fourth, there is an influence between self-confidence, learning interests, and parental support on the ability to speak on the material of the student's negotiation text based on Sig grades. 0.001, each with a test significance level of 5% (α=0.05).